Activity of the supernexid dismutase Cu /Zn in seminal plasma and integrity of plasmatic membrane in semen of boar (Sus scrofa domestica) conserved with melatonin (Gaceta de Ciencias Veterinarias, 2018)
The objective of this research is to determine the effect of melatonin on superoxide dismutase (SOD) in seminal plasma and sperm membrane integrity during storage at 16°C. Methodology: Boar seminal samples were taken between 7-18 months of age using manual technique of gloved hand extraction in Inversiones Porcinas C.A. The optimal samples were diluted and aliquoted: control (with diluent), vehicle control (diluent and ethanol), semen with melatonin (1.25 mM), aliquots being stored at 16ºC for subsequent evaluation at day 0 and 1 of the preparation. The enzymatic activity of SOD (commercial kit Cayman®) and membrane integrity (hypo-osmotic test) was evaluated. The results were analyzed by means of ANOVA, with statistical package SPSS 15.0 for Windows with p
Keywords: SOD; semen; membrane integrity; melatonin